1965
DOI: 10.1109/thfe.1965.6591255
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models of human operators in simple two-axis manual control systems

Abstract: An application of continuous parameter optimization techniques to the synthesis of a model of human tracking behavior in a simple two-axis task is presented. Considerable emphasis is placed on the measurement of performance criteria for estimating the relative difficulty of single-axis and two-axis tasks as well as for evaluation of the validity of mathematical models. It is shown that the modeling technique can be used to yield a quantitative indication of the degree of cross coupling between axes introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…It has been shown that the human operator 1s able to use the statistical characteristics of the input signal and the dynamic characteristics of the other elements of the system to adjust (shape) his response [2][3][4][5][6][7] characteristics in order to match the behavior of the control situations [16][17][41][42][43][44].…”
Section: Controlled Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the human operator 1s able to use the statistical characteristics of the input signal and the dynamic characteristics of the other elements of the system to adjust (shape) his response [2][3][4][5][6][7] characteristics in order to match the behavior of the control situations [16][17][41][42][43][44].…”
Section: Controlled Systemmentioning
confidence: 99%
“…It means that we can not extract any noise-free information from the measurements; all components of y(t) are corrupted by [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] notse. Further, it is assumed that w(t), v(t) and x(to) are independent and Gaussian with 25) and W(t) is nonnegative definite symmetric matrix.…”
Section: Solution Of the Noise-free Regulator Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications dealt with the pilot´s response to various stimuli. The focus was mainly on the pilot's response to low-frequency stimuli and traffic delays in relation to flight dynamics [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of four different models is tracked. The publication [3] deals with the description of the pilot's behaviour in the system of two degrees of freedom related to longitudinal and lateral control. The experiment was performed on each axis separately, the maximum excitation frequency was about 16 Hz.…”
Section: Introductionmentioning
confidence: 99%